A framework of blockchain technology adoption: An investigation of challenges and expected value - Toufaily, Elissar; Zalan, Tatiana; Dhaou, Soumaya Ben (Information & management, 2021)
The purpose of the paper is to investigate the challenges and implications related to blockchain adoption in the private and public sectors, and from the entrepreneurs’ perspective. Based on 46 semi-structured interviews, a data-driven conceptual framework is proposed focussing on the environmental, organizational and technological challenges of blockchain adoption. The framework includes expected socio-economic value of blockchain adoption at the ecosystem level from a multi-stakeholder perspective: organizations and industries, end-users and society, public sector, and start-ups and entrepreneurs. The paper highlights the differences between permissioned and permissionless blockchains and identifies new constructs in blockchain technology adoption.